Analysis Of The Characteristics And Interests Of The Community In Using Public Transportation In Purworejo Regency - Muhammad Isnu Bilhalal; Femmy Sofie Schouten; Librita Arifiani (Politeknik Transportasi Darat Indonesia - STTD Bekasi, 2025)
This study analyzes the characteristics and interests of the community in using rural transportation in Purworejo Regency, with a focus on rural transportation. The background of this research is a significant decrease in the number of fleets and passengers in recent years. This decline in interest is caused by several factors including tariff uncertainty, low load factor, increased private vehicle ownership and the emergence of new modes of transportation such as Transjateng BRT. The purpose of this study is to identify and analyze the factors that affect people's interest in using rural transportation and recommend efforts to increase this interest. This study uses a quantitative approach with primary data collected through questionnaires from 400 respondents. The variables studied include accessibility, safety, tariffs, and service quality The data analysis method used is (SEM) based on Partial Least Squares (PLS) with SmartPLS 4.0 software. The results of the analysis show that several findings of the Inter-Variable Relationship, namely Accessibility, safety, and tariffs, are proven to have a positive and significant effect on service quality. Accessibility, safety, fares, and service quality directly have a positive and significant effect on public interest in using public transportation. Based on these findings, it is recommended to improve accessibility, safety, reasonable rates, and consistent service quality as the main keys to increase public interest, especially students/students in using rural public transportation. The suggested strategies include schedule adjustments, special fare subsidies for students, integration with the Trans Jateng BRT, as well as periodic monitoring and evaluation involving user participation.